2007
DOI: 10.1590/s1413-86702007000100031
|View full text |Cite
|
Sign up to set email alerts
|

Paragonimiasis: first case reported in Brazil

Abstract: The authors present a case from a 59 years old white female Brazilian patient, based in Salvador-Bahia, Brazil's northeastern side area, who experienced irritative cough and progressive dyspnea, and, after 18 months, was admitted to a hospital with respiratory insufficiency. The physical exam showed diffuse rales in both hemithoraces. Initial leukogram showed 14,400 cells/µ µ µ µ µL with 14% of eosinophils and chest X-ray showed peribronchovascular infiltrate,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Patients from endemic areas frequently present with a subacute to chronic cough, often mildly productive with blood-streaked sputum [140-143]. Up to 17% of patients with lung infections have no symptoms [33].…”
Section: Eosinophilia In Indigenous Population (Immigrant/refugeementioning
confidence: 99%
“…Patients from endemic areas frequently present with a subacute to chronic cough, often mildly productive with blood-streaked sputum [140-143]. Up to 17% of patients with lung infections have no symptoms [33].…”
Section: Eosinophilia In Indigenous Population (Immigrant/refugeementioning
confidence: 99%
“…Salmon is considered an intermediate host for tapeworms, such as Diphyllobothrium latum , and nematodes, such as Anisakis spp., which can be transmitted to humans (Nawa et al, 2005). Incidences of intestinal capillariasis (Ahmed et al, 1999; Austin et al, 1999) and paragonimiasis (Lemos et al, 2007) have been reported in humans who had consumed salmon. These diseases occur in either directly due to ingestion of viable parasites or as hypersensitive reactions against parasite antigens.…”
Section: Introductionmentioning
confidence: 99%
“…It also occurs in humans via ingestion of raw meat from wild boars or other paratenic hosts, particularly in Japan [2,3]. Recently, cases of paragonimiasis have been reported in almost every country in the world [4][5][6][7], because of increased numbers of immigrants [8] and overseas travelers, the popularization of ethnic dishes in developed countries [9], and the expansion of the international food trade [2,3].…”
Section: Introductionmentioning
confidence: 99%